Adverse drug events in Chinese elder inpatients: a retrospective review for evaluating the efficiency of the Global Trigger Tool - Yu, Nan; Wu, Liuyun; Yin, Qinan; Du, Shan; Liu, Xinxia; Wu, Shan; Tong, Rongsheng; Yan, Junfeng; Bian, Yuan (Frontiers in Medicine, 2023)
Background: Elderly patients frequently experience a high incidence of adverse drug events (ADEs) due to the coexistence of multiple diseases, combination of various medications, poor medication compliance and other factors. Global Trigger Tool (GTT) is a new method for identifying ADEs, introducing the concept of trigger, that is, clues including abnormal laboratory values, reversal drugs and clinical symptoms that may suggest ADEs, and specifically locating information related to ADEs in the medical record to identify ADEs. The aim of this study was to establish a GTT-based trigger tool for adverse medication events in the elderly, and to investigate the risk variables associated with such events.The triggers were identified by reviewing the frequency of ADEs in elderly patients in Sichuan, China, retrieving relevant literature and consulting experts. A retrospective analysis was carried out to identify adverse medication occurrence among 480 elderly inpatients in Sichuan People's Hospital.Results: A total of 56 ADEs were detected in 51 patients (10.62%), 13.04 per 1, 000 patient days, and 11.67 per 100 admissions. The overall positive predictive value (PPV) of the triggers was 23.84%. 94.64% ADEs caused temporary injury. Gastrointestinal system injury (27.87%) and metabolic and nutritional disorders (24.53%) were the primary organ-systems affected by ADEs. The majority of ADEs were caused by drugs used to treat cardiovascular diseases. 71.43% of ADE occurred within 2 days of administration and the risk factor analysis of ADE revealed that the number of medicines had significant correlation.This study demonstrated that the GTT's value as a tool for ADEs detection in elderly inpatients in China. It enhances the level of medication management and comprehensively reflects the situation of ADE of the elderly.